DINAMIKA ISLAM INDONESIA: MEDIA MASSA SEBAGAI INSTRUMEN GERAKAN - Khusairi, Abdullah (Universitas Islam Negeri Raden Intan Lampung, 2018)
The history of Islamic dynamics in Indonesia has been widely seen through educational instruments, trade routes, and networks of tarekat scholars. Still few see the mass media as a motion instrument. In fact, growing Islamic thoughts and movements in a place, also possible occurred on the insiprasi elsewhere through the mass media. The character of mass media capable of arousing the public subconscious has been used by Muslim scholars to jointly build a line against colonialism and liberate the nation. The mass media of colonialism became a means of struggle. Wahana conveyed his aspirations to the government and also played a role in educating the community. Unlike now, where the mass media has become a larger industry, in the past, the print media media in particular became the foundation of the actual information rides for the intellectuals who have not put forward the industry side